Unlocking Gen Z: the power of compassionate teaching - Hasan, Nor Haniza; Shafeei, Khairon Nisa (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2025)
In today’s educational environment, teaching extends beyond knowledge transfer to fostering a supportive, compassionate classroom, especially for Generation Z students. Characterized by tech-savviness, social and mental health awareness, and high rates of anxiety and burnout, Gen Z requires approaches that prioritize emotional well-being alongside academic growth. Research shows that excessive screen time and fear of missing out negatively impact their well-being (Smith & Lee, 2025), while compassionate teaching creating a welcoming environment where students feel valued and understood enhances engagement, motivation, and academic performance (Dyer et al., 2023; Gorny-Wegrzyn & Perry, 2021). By acknowledging students’ emotional needs, educators can cultivate both personal and academic success in this generation.